New Variant of Cottage Cheese − Use of the Design Thinking Method - Wilk, Marta; Nowak, Marianna (Nowy wariant serka wiejskiego − wykorzystanie metody design thinking, 2024)
Aim: In today's dynamically developing food market, manufacturers face numerous challenges. In the dairy sector there is a growing interest in innovative products that can interest and attract consumers. The aim of the work was to develop a new variant of cottage cheese using the design thinking method. Methodology: The method used emphasises placing the consumer at the centre of the design process and taking into account their needs and preferences. The correct implementation of this method includes several stages: understanding the consumer's needs, identifying problems, generating ideas, prototyping and testing. Results: As a result of the conducted research, the target group was determined and a new product was designed, namely cottage cheese with the addition of pumpkin mousse with a hint of cinnamon. The product was positively assessed during the organoleptic evaluation and recognised as a novelty. Implications and recommendations: The presented research results suggest that work on innovative food products should be continued, both in terms of the use of commonly known and completely new varieties of plant raw materials with high sensory values for consumers. Originality/value: The product proposed in this paper is a novelty among the assortment available on the market. The application of the design thinking method to the development of cottage cheese with the addition of vegetables as a sweet addition is the first attempt of this type.
Nauki Inżynierskie i Technologie = Engineering Sciences and Technologies, 2024, Nr 40, s. 53-61